Hydrochemical dynamics of stream following rainfall events at agricultural catchments in New Zealand - Yulianti, Meti; Murray, Rachel (BRIN Publishing, 2023)
One of the prerequisites for efficiently managing lake water quality is reliable data regarding the quantity and quality of inflows water, mainly the export of nutrients from the catchment area during rainfall events. We investigated the dynamic characteristics of hydrochemicals concerning rainfall events in agricultural stream waters flowing into eutrophic lakes situated on the North Island’s central plateau of New Zealand. We utilized isotopic composition of water (δ2H-H2O and δ18O-H2O) and nitrate (δ15N-NO3- and δ18O-NO3-) along with high-frequency hydrochemical data for source identification of water and nitrate during a drought period (2020). Our findings indicate that it is essential to initially grasp the fundamental mechanisms associated with rainfall events to formulate effective strategies for minimizing nutrient losses. The methodology outlined in this research integrates stable isotope hydrology with water quality monitoring initiatives, facilitating the understanding and managing the primary governing mechanisms behind diverse contaminant losses from land to adjacent water bodies, explicitly focusing on nitrates. This approach establishes a framework that can assist in devising measures for water quality improvement capable of anticipating the repercussions of substantial rainfall events more effectively.